Standardization of Antigen-Emulsion Preparations for the Induction of Autoimmune Disease Models - Topping, Louise M.; Romero-Castillo, Laura; Urbonaviciute, Vilma; Bolinsson, Hans; Clanchy, Felix I.; Holmdahl, Rikard; Bäckström, B. Thomas; Williams, Richard O. (Frontiers in Immunology, 2022)
Autoimmune murine disease models are vital tools for identifying novel targets and finding better treatments for human diseases. Complete Freund’s adjuvant is commonly used to induce disease in autoimmune models, and the quality of the adjuvant/autoantigen emulsion is of critical importance in determining reproducibility. We have established an emulsification method using a standard homogenizer and specially designed receptacle. Emulsions are easy to prepare, form stable and uniform water-in-oil particles, faster to make than the traditional syringe method, use less material and are designed to fill syringes with ease. In the present study, we have validated the emulsions for induction of experimental autoimmune encephalitis, collagen II induced arthritis, antigen induced arthritis, and delayed type hypersensitivity model. These models were induced consistently and reproducibly and, in some cases, outperformed the syringe-based method. The method described herein is simple, cost-effective and will reduce variability, thereby allowing for reduced numbers of animal used.